Marie Corelli, Wormwood, and the Diversity of Decadence - Jessica DeCoux (Cahiers Victoriens et Edouardiens)
Marie Corelli was, in her day, a wildly popular best-selling author and public figure, one who captured the public’s imagination with her dramatic and fantastical novels. Her great popularity and the apparently moralistic elements of her work have excluded her from the ranks of the fin-de-siècle British Decadents, a group (such as it exists) traditionally defined by its rejection of mainstream middle-class values and its desire to appeal to a select readership of aesthetically-minded intellectuals. Indeed, Corelli’s novel Wormwood is generally read as an anti-Decadent creed, or at the very least a novel which disingenuously castigates Decadence while titillating readers with themes and tropes “co-opted” from works of that genre.In fact, Wormwood is so often read in these terms because it eludes easy interpretation, a quality that marks it as a distinctly Decadent text. Corelli’s condemnation of the absintheur as a failed Decadent is a call not to moral orthodoxy, but to another, less recognizable but equally subversive model of Decadence. Some of the doubts the novel raises about the Decadent project and the troubled place of the Decadent in the nineteenth-century popular imagination are echoed by other Decadent works of the time.Reading Corelli’s novel in this way not only allows for a dramatic rethinking of her work, it also opens up a reconsideration of the ways that Decadence was embraced by the fin-de-siècle literary public, and the ways that public did not merely consume Decadence but refined and disseminated it. This reading also raises the possibility that the Decadent practice of drawing the boundaries of genre in tight and exclusionary ways served to encourage the production of numerous Decadences.